Tri1 Encodes the Cytochrome P450 Monooxygenase for C-8 Hydroxylation during Trichothecene Biosynthesis in Fusarium sporotrichioides and Resides Upstream of Another New Tri Gene - Meek, Isaac B. (American Society for Microbiology, 2003)
Many Fusarium species produce one or more agriculturally important trichothecene mycotoxins, and the relative level of toxicity of these compounds is determined by the pattern of oxygenations and acetylations or esterifications on the core trichothecene structure. Previous studies with UV-induced Fusarium sporotrichioides NRRL 3299 trichothecene mutants defined the Tri1 gene and demonstrated that it was required for addition of the oxygen at the C-8 position during trichothecene biosynthesis. We have cloned and characterized the Tri1 gene from NRRL 3299 and found that it encodes a cytochrome P450 monooxygenase. The disruption of Tri1 blocks production of C-8-oxygenated trichothecenes and leads to the accumulation of 4,15-diacetoxyscirpenol, the same phenotype observed in the tri1 UV-induced mutants MB1716 and MB1370. The Tri1 disruptants and the tri1 UV-induced mutants do not complement one another when coinoculated, and the Tri1 gene sequence restores T-2 toxin production in both MB1716 and MB1370. The DNA sequence flanking Tri1 contains another new Tri gene. Thus, Tri1 encodes a C-8 hydroxylase and is located either in a new distal portion of the trichothecene gene cluster or in a second separate trichothecene gene cluster.